Self-managed work teams: an enabling or coercive nature - Proença, Teresa (2013)
The paper analyses self-managed work teams (SMWTs) of two Portuguese industrial firms, using the case-study method. It examines the nature of SMWTs, by discerning a double enabling and coercive face. The enabling features are related to high levels of job enrichment, broad employee participation, and extensive communication. The coercive features are related to incidental job rotation to optimize technology, asymmetries of technical knowledge between supervisors or industrial engineers and team members, economic cohesion based upon the group-performance system and peer pressure toward self-discipline. An enabling face of SMWT has greater chances to prevail under an organizational infrastructure based upon management commitment regarding economic, cultural and social objectives of SMWTs, management ability to develop a set of complementary and mutually reinforcing HR practices and production programs aligned with SMWTs, as well as a past history and employees’ past experience in tune with present changes.